The Current and Potential Future Role of Postmortem Computed Tomography in Medicolegal Death Investigation. Issue 4 (December 2015) - Daly, Barry; Andrews, Sam; O'Donnell, Chris
The development of whole body, high resolution postmortem computed tomography (PMCT) with three-dimensional depiction has led some authors to describe the concept of "virtual autopsy" as a noninvasive replacement to conventional autopsy. A realistic appraisal of the capabilities of PMCT suggests its true role is more complex – in some settings such as accidental blunt trauma it has the potential to circumvent conventional autopsy and in others such as severe burns or drowning, PMCT can act as a triage tool to determine if autopsy is required. In many other cases, PMCT has a role of adjunct to conventional autopsy. Despite its myriad potential applications, PMCT remains underutilized in many countries. This paper addresses the background of PMCT, and describes its strengths, weaknesses, and indications. It discusses the economic and logistical challenges to its introduction, and emphasizes the clinical cooperation between diagnostic radiologists and forensic pathologists, and the training initiatives that are necessary for its success.